2024
DOI: 10.2186/jpr.jpr_d_22_00266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of support structures on the trueness and precision of 3D printing dentures: An <i>in vitro</i> study

Abstract: Additive manufacturing has revolutionized the fabrication of complete dentures. However, this process involves support structure, which is a construction part that holds the specimen during printing, and may prove to be disadvantageous. Therefore, this in vitro study compared the effect of support structure reduction on various volume and area distributions of a 3D-printed denture base to determine optimal parameters based on accuracy. Methods: A complete maxillary denture base construction file was used as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The importance of the three samples does not have large deviations, so the support design has little effect on the tensile strength of this material. Namano S. et al [5] showed that with the same printing angle, the number of support structures and their distribution have little effect on the printed part result. Reducing support has a relatively small impact on accuracy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the three samples does not have large deviations, so the support design has little effect on the tensile strength of this material. Namano S. et al [5] showed that with the same printing angle, the number of support structures and their distribution have little effect on the printed part result. Reducing support has a relatively small impact on accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…The SLA operation procedure is carried out as follows: In a photopolymer liquid tank, the print tray is submerged in a bath of liquid resin solution a fragile distance from the liquid surface (the tray is covered with a layer of liquid resin). The UV rays shine directly through the UV reflectors on the support tray, curing the liquid layer into a solid forming a precise cross-section of the part [2][3][4][5][6][7][8][9]. After each print layer is solidified, the print tray moves by one step, equal to the thickness of the print layer in the liquid, and the re-sweeping blade distributes the resin upwards in preparation for the formation of a new print layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have revealed that 3D-printed dentures have no significant difference either in fitting onto mucosal surfaces compared to conventional dentures, or in wear resistance of artificial teeth compared to conventional hard resin teeth, thereby indicating that they can be applied clinically. Furthermore, it is possible to decrease the costs by reducing the support structure unique to 3D-printed denture modeling, without compromising accuracy [5]. In a super-aged society such as Japan, the demand for 3D-printed dentures that can be produced inexpensively and efficiently is expected to increase.…”
Section: Milled Dentures and 3d-printed Denturesmentioning
confidence: 99%